Pengaruh Model Pembelajaran Inkuiri Berbasis Siklus Tri Pramana pada Mata Pelajaran IPAS terhadap Kemampuan Berpikir Kritis dan Pemecahan Masalah Siswa Kelas V di SD Negeri 2 Selat - I Komang Adi Suarjana; Kadek Suranata; Ni Made Dainivitri Sinta Sari (STKIP Subang, 2026)
Elementary school students’ problem-solving abilities are still relatively low because the learning process tends to be teacher-centered and does not actively involve students in discovering learning concepts. This condition causes students to have difficulty thinking critically, creatively, and independently in solving problems. This study aims to determine the effect of the inquiry learning model on students’ problem-solving abilities in elementary schools. This study employed a quantitative approach with a quasi-experimental research design. The subjects of the study were elementary school students divided into experimental and control groups. Data collection was conducted using a test method in the form of problem-solving ability questions. The data were analyzed using prerequisite tests, namely normality and homogeneity tests, followed by hypothesis testing using the t-test. The results showed that the inquiry learning model had a positive effect on students’ problem-solving abilities. Students who learned through the inquiry learning model demonstrated better critical thinking skills, active questioning, and the ability to find solutions to given problems compared to students who learned through conventional learning. Therefore, the inquiry learning model is effective in improving elementary school students’ problem-solving abilities.